Pembentukan karakter melalui manajemen pembiasaan di sekolah dasar islam terpadu Ihsanul Fikri Kota Magelang - Nurjani Nurjani; Mundilarno Mundilarno (Universitas Sarjanawiyata Tamansiswa, 2016)
This research aims to: 1) determine the applied management education in elementary habituation IT Ihsanul Fikri Magelang in efforts to establish the character of students. 2) determine the effectiveness of the formation character students through the habituation Management. 3) identify supporting factors and inhibiting factors in the implementation of the habituation management. This study is a qualitative study conducted in SDIT Ihsanul Fikri Magelang. The subjects in this study include principals and vice-principals, teachers, students, parents and school committee. Data collection techniques used in this study are the observation, interview, and documentation. Data analysis techniques in this study include reduction data, display/presentation of the data and drawing conclusions. The validity of the data is conducted by using a triangulation technique to check the validity of the data. The results of the study concluded: 1) Management form of habituation: a.Planning the conditioning program in the character formation of students in SDIT Ihsanul Fikri has been good. b. Organizing management has been firmly habituation, which is the principal in charge, assisted by student vice minister, curriculum vice minister, builder habituation and the class teacher and supported by all components of the school. c Application of management is suited to the type of habituation.Routine habituation routinely is done every day on a regular basis, habituation programmed predetermined schedule. .d Evaluation of habituation management: Management of habituation in SDIT Ihsanul Fikri Magelang already well underway. 2) The formation of character through habituation runs effectively proved to be known and The character values are done in daily life. 3) The supports factors habituation management among others the existence of good habitual programme, infrastructure, human resources, parents supports and the school committeeâ€™s ones. The obstacles are less of proper infrastructure, Â less concerned parents, any Part of teachers and employees are less concerned, the existence of communities that are less appropriate to educationâ€™s character.